Saúde mental e afetos de mulheres encarceradas por tráfico de drogas - Puech, Ana Maria Collete Chalfun (2023)
Mental disorders are a prevalent health problem in women living in prisons. However, notably in the field of psychology, there is a gap with regards to academic production that addresses this topic from the perspective of this population. This work aimed to investigate possible mental suffering and affective states in women incarcerated for drug trafficking or association with trafficking in a Brazilian state penitentiary. A sequential mixed research method was carried out, with an initial phase based on the collection and analysis of quantitative information obtained through SRQ-20 and PANAS scales. This stage comprised 93 participants, including those who were convicted or awaiting sentence for other crimes, aiming at the safety of all and in order to avoid the outbreak of conflicts between factions. The results showed that the vast majority of participants experiences high levels of mental distress, with no statistically significant differences being found between the two groups (drug trafficking group – GTD and other crimes group – GO). The second phase included semi-structured interviews with seven GTD participants, identified from the quantitative results as clusters representatives. The following thematic categories were raised: violence (dysfunctional family, violent partners and association to crime); maternal suffering; risk behavior; mental suffering (guilt and regret, fear and powerlessness, stress and alertness); containment and explosion; affective losses (institutional abandonment, loss of affective bonds; and hope. The reports, analyzed from the theoretical perspective of analytical psychology, revealed a history marked by fragile family structures, which ended up determining immature personalities, with tendencies towards impulsivity and behavior of risk, with emphasis on drug addiction, suicidal ideation and acts of self-mutilation. We concluded that, if previous social circumstances of these women are not the most favorable for mental health, the prison experience does not contribute to alleviate their suffering, to say the least. Imprisonment under the conditions found perpetuates the violence in their lives and makes them feel disqualified and powerless to change the course of their lives